การศึกษาและวิจัยสลักเหล็กทดแทนสลักอะลูมิเนียมที่ชำรุดของสะพานทหาร เอ็ม จี บี - ธัญญลักษณ์ เอี๊ยสกุล (สภาคณาจารย์ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2022)
In the military, bridges are important equipment for deploying troops into combat areas. It is also useful in urgent emergency applications. Including road construction or natural disasters, such as floods, which cause the road is cut therefore use the military bridge to solve problems and alleviate the suffering for the victims. At present, the MGB Military Bridge is damaged in the pin of the bridge, as a result Bridge is not working. The material used to make the bridge is not manufactured because it is a military secret of the country of production. The purpose of this research was to study the shear and moment behavior of the MGB Military Bridge and to compare the results and analyze it with the shear force and bending moment studied to find steel material to replace the damaged aluminum material.